Green competence framework: evidence from China - Subramanian, Nachiappan; Abdulrahman, Muhammad D.; Wu, Lin; Nath, Prithwiraj (Taylor and Francis, 2015)
Recently human resources management functions such as recruitment, selection, training and performance evaluation are expected in considering environmental management issues. Environmental protective acts with adequate ecological knowledge and socio-economic behavior and skills are referred to in this paper as green competencies (GCs). However, a systematic approach for developing and understanding key factors that enhance individuals' GCs is lacking. This study contributes to green human resource literature by integrating environmental consumer behavior literature with traditional skills and competencies literature to help firms to select the right individuals to achieve their environmental goals. Using Robert's competencies framework and structural equation modeling, this paper empirically examines the influence of individual GCs on organizations' green practices and performance objectives. Our model is tested using a sample of 1230 employees working in key industries in the Chinese coastal city of Ningbo. The results indicate that acquired GCs are more positively associated with individuals' GCs and green behavior. The study empirically demonstrates that verifying acquired GC attributes such as environmental knowledge, green purchase attitude and intention during employee selection would certainly be helpful for firms to identify individual green performance potential.